MCM9 deficiency delays primordial germ cell proliferation independent of the ATM pathway. Issue 11 (14th October 2015) - Luo, Yunhai; Schimenti, John C.
Summary: Maintenance of genome integrity is crucial for the germline, and this is reflected by lower mutation rates in gametes than somatic cells. Germ cells at different stages employ different DNA damage response (DDR) mechanisms. In response to certain DNA repair defects, primordial germ cells (PGCs) either undergo apoptosis or delayed proliferation, although little is known about the underlying mechanisms that govern these outcomes. Here, we report genetic studies of DDR pathways that underlie germ cell depletion in mice mutant for minichromosome maintenance 9 ( Mcm9 ), a gene that plays a role in homologous recombination repair (HRR). Germ cell depletion in these mice is a result of reduced PGC numbers both before and after they arrive in the primitive gonads. This reduction was attributable to reduced proliferation, not apoptosis, and this response was independent of ATM‐CHK2‐TRP53‐P21 signaling. This mechanism of PGC depletion differs from that in Fancm mutants, which also display reduced PGC depletion that is partially orchestrated by the ATM‐TRP53‐P21 pathway. Germ cell depletion in mice doubly deficient for FANCM and MCM9 was additive, indicating that the damage caused by each mutation triggers different DDR pathways to slow the cell cycle as a means to preserve genomic integrity. genesis 53:678–684, 2015. © 2015 Wiley Periodicals, Inc.